Understanding the methylammonium chloride-assisted crystallization for improved performance of lead-free tin perovskite solar cells - Cuzzupè, Daniele T.; Öz, Senol Dilara; Ling, Jinkiong; Illing, Elias; Seewald, Tobias; Jose, Rajan; Olthof, Selina; Azhar, Fakharuddin; Schmidt-Mende, Lukas (John Wiley and Sons Inc, 2023)
In the quest for perovskite materials with reduced toxicity, Sn perovskites are emerging. However, they suffer from material instability and rapid crystallization, leading to high defect densities in the films. In this work, the methylammonium chloride (MACl)-assisted crystallization as a route to improve stability and optoelectronic quality of quasi 2D/3D PEA0.08FA0.92SnI3 perovskite is demonstrated. For an optimal additive amount (10 mol%), a 37% increase in power conversion efficiency is found. Notably, MACl enhances the films' stability, evidenced by temporal PL tracking. Understanding the effect of MACl addition in this system is interesting for the pursuit of efficient and stable tin-based devices. The investigations show that MACl addition causes a shift in the optical bandgap and improves morphology, indicating effects in the bulk crystal structure. X-ray photoelectron spectroscopy confirms the presence of Cl on the surface, but no indication of MA+ is found. Intriguingly, UV photoelectron spectroscopy shows pronounced changes in the density of states. For the first time, it is shown that MACl promotes the formation of a two-dimensional layer via the surface accumulation of PEA+. The MACl additive lowers the absorber's ionization energy, possibly facilitating hole extraction. Overall, this work highlights a facile route to control the crystallization of Sn perovskites.